General Index of Issues 61-70 - Gapper, Sherry E. (2021)
The General Index of issues from 61 to 70  shows the growing interest of the academic community in carefully and meticulously approaching the material and intangible cultural heritage of our group of republics through the production of studies on Central American letters, linguistics, Spanish, and various indigenous languages, as well as with proposals on foreign languages in Costa Rica coming from the perspective of applied linguistics.